Online Paraphrasing Tools in Language Learning: Students’ Perceptions to Overcome the Difficulties in Academic Writing - Riski Abi Harnoyo (English Language Education, Universitas Internasional Batam, 2024)
This research aims to analyze the students' perception of using online paraphrasing tools to overcome their difficulties in academic writing. The participants were 23 university English as a Foreign Language (EFL) students at a Central Java, Indonesia private university. The students were from batches 2019, 2020, and 2021, and they used online paraphrasing tools to help them in their academic writing journey in various academic writing-related classes, such as Academic Writing, Research Design, Research Instrument Design, and Research Report. The data were collected through close-ended questionnaires using the Four-Likert scale (i.e., Strongly Agree, Agree, Disagree, and Strongly Disagree). The data analysis indicated that positive students' perceptions of online paraphrasing tools to overcome the difficulties in their academic writing. Moreover, by applying online paraphrasing tools, students can overcome difficulties in their academic writing. The study also reported students' positive perceptions that using online paraphrasing tools might help to improve their academic writing quality and make them more confident in writing academically.